2006
DOI: 10.2166/wh.2006.0020
|View full text |Cite
|
Sign up to set email alerts
|

Toxic cyanobacteria and their toxins in standing waters of Kenya: implications for water resource use

Abstract: Phytoplankton biodiversity studies in Kenya's standing waters were carried out between 2001 and 2003. Toxin producing cyanobacteria were recorded in twelve water bodies. Microcystis and Anabaena were the most common species in freshwaters while Anabaena and Anabaenopsis were common in alkaline saline lakes. Seven lakes with cyanobacteria blooms and a hot spring had detectable levels of microcystins and anatoxin-a. Cell bound microcystins (LR equivalents) concentration ranged from 1.6-19800 microgg(-1) Dry Weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 32 publications
(29 reference statements)
3
43
0
1
Order By: Relevance
“…Some algae can produce toxins that are associated with human health problems [23]. Thus, the analysis of phosphorus in sediments from the lake is critical.…”
mentioning
confidence: 99%
“…Some algae can produce toxins that are associated with human health problems [23]. Thus, the analysis of phosphorus in sediments from the lake is critical.…”
mentioning
confidence: 99%
“…Despite this, there is no historical precedent of the people surrounding Lake Bogoria having used Spirulina as a food source. There have been conflicting reports, however, of whether Lake Bogoria Spirulina produces microcystins, a group of hepatotoxins that is highly hazardous to human health [13]. While certain studies conclude that Lake Bogoria Spirulina might be a source of microcystins, other studies could not find significant levels of them [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There have been conflicting reports, however, of whether Lake Bogoria Spirulina produces microcystins, a group of hepatotoxins that is highly hazardous to human health [13]. While certain studies conclude that Lake Bogoria Spirulina might be a source of microcystins, other studies could not find significant levels of them [13,14]. Should Lake Bogoria Spirulina be toxin-free, then it has the potential to serve as a local, sustainable means of addressing undernutrition in the Lake Bogoria region.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies in several European and Asian countries revealed that MCs were present in 60% to 90% of all samples investigated (Chorus 2001;Kotut et al 2006). In China, problems associated with cyanobacteria are increasing, especially in areas with increasing environment pollution and inadequate water treatment due to population growth (Jin 2003;Xu et al 2007).…”
Section: Introductionmentioning
confidence: 99%